Reorganização do espaço na colónia de Moçambique. Estudo do fenómeno urbano - Iglésias, Olga (Africana Studia, 2020)
In the present text, we will analyse the urban phenomenon as a result of the impact of the Portuguese settling throughout the centuries XIX and XX. The starting question was suggested to us while we were selecting the information: How was Mozambique’s space organized in the colonial time? The raised hypotheses were: Did the occupation allow a transposition of the Portuguese urban model or did it lead to an adaptation with African elements? The purpose of the research: to rethink the city as a place of cultural melting pot, revisiting the oral, the written and the iconographic sources.